2018
DOI: 10.1101/492108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical excitation:inhibition imbalance causes abnormal brain network dynamics as observed in neurodevelopmental disorders

Abstract: AbstractAbnormal brain development manifests itself at different spatial scales. However, whether abnormalities at the cellular level can be diagnosed from network activity measured withfunctional magnetic resonance imaging (fMRI) is largely unknown, yet of high clinical relevance. Here we applied fMRI while using chemogenetics to increase the excitation-to-inhibition ratio (E:I) within cortical microcircuits of the mouse brain, thereby mimicking a putative mechanism of neurode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 96 publications
2
27
0
Order By: Relevance
“…The recent development of a modular set of evolved G protein-coupled receptors, termed Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) has greatly expanded the capabilities of this approach (Armbruster et al, 2007;Alexander et al, 2009;Lee et al, 2014;English and Roth, 2015;Roth, 2016;Sciolino et al, 2016;Smith et al, 2016;Zhu et al, 2016;Aldrin-Kirk et al, 2018). Like optogenetics, chemogenetics is readily MRI compatible (Giorgi et al, 2017;Roelofs et al, 2017;Chen et al, 2018;Griessner et al, 2018;Markicevic et al, 2018). Despite its potential, there is, however, an ongoing debate about the specificity of chemogenetics ligands both in neurobehavioral studies (MacLaren et al, 2016;Gomez et al, 2017;Mahler and Aston-Jones, 2018;Manvich et al, 2018) and in chemo-fMRI applications (Giorgi et al, 2017), thereby requiring rigorous methodology to control for potential off-target effects.…”
Section: Chemogeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent development of a modular set of evolved G protein-coupled receptors, termed Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) has greatly expanded the capabilities of this approach (Armbruster et al, 2007;Alexander et al, 2009;Lee et al, 2014;English and Roth, 2015;Roth, 2016;Sciolino et al, 2016;Smith et al, 2016;Zhu et al, 2016;Aldrin-Kirk et al, 2018). Like optogenetics, chemogenetics is readily MRI compatible (Giorgi et al, 2017;Roelofs et al, 2017;Chen et al, 2018;Griessner et al, 2018;Markicevic et al, 2018). Despite its potential, there is, however, an ongoing debate about the specificity of chemogenetics ligands both in neurobehavioral studies (MacLaren et al, 2016;Gomez et al, 2017;Mahler and Aston-Jones, 2018;Manvich et al, 2018) and in chemo-fMRI applications (Giorgi et al, 2017), thereby requiring rigorous methodology to control for potential off-target effects.…”
Section: Chemogeneticsmentioning
confidence: 99%
“…Both hM3Dq and hM4Di DREADDs are classically activated with infusion of the effector clozapine-N-oxide (CNO) (Armbruster et al, 2007;Alexander et al, 2009;Roth, 2016;Smith et al, 2016;Giorgi et al, 2017;Markicevic et al, 2018), but new evidence suggests that CNO does not cross the bloodbrain barrier and instead is back-metabolized in vivo into its precursor, clozapine (Gomez et al, 2017;Mahler and Aston-Jones, 2018;Manvich et al, 2018). Importantly, unlike CNO, clozapine is a psychoactive drug, that possesses an affinity for many endogenous receptors.…”
Section: Chemogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…We kept mice under light isoflurane anesthesia (see methods) and recorded 15 min of baseline fMRI, before activating hM3Dq with clozapine (0.03 mg/kg, i.v.) 40 . After the clozapine injection, we continued the fMRI recordings for 8 minutes (i.e.…”
Section: Lc Activation Drives Rapid Increases In Functional Connectivitymentioning
confidence: 99%
“…We observed that inhibition of the anterior cingulate area, which has been identified as a hub region (i.e., a highly interconnected brain region), resulted in largescale neuronal activity modulations as well as functional connectivity alterations (Peeters et al, 2019). Furthermore, other recent studies combined chemogenetics with resting-state functional MRI in order to evaluate functional connectivity alterations after modulation of the excitation-inhibition balance in the somatosensory cortex (Markicevic et al, 2018) or to assess the effects of selective stimulation of the locus coeruleus with hM3Dq on a large-scale functional connectivity (Zerbi et al, 2019). Giorgi et al (2017) highlighted the advantage of chemogenetics combined with functional MRI to causally link the activity of specific neuronal populations with whole-brain functional activity.…”
Section: Dreadds Combined With Mrimentioning
confidence: 90%